2016
DOI: 10.1371/journal.pone.0156817
|View full text |Cite
|
Sign up to set email alerts
|

Altered Crossover Distribution and Frequency in Spermatocytes of Infertile Men with Azoospermia

Abstract: During meiosis, homologous chromosomes pair to facilitate the exchange of DNA at crossover sites along the chromosomes. The frequency and distribution of crossover formation are tightly regulated to ensure the proper progression of meiosis. Using immunofluorescence techniques, our group and others have studied the meiotic proteins in spermatocytes of infertile men, showing that this population displays a reduced frequency of crossovers compared to fertile men. An insufficient number of crossovers is thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…A reduced number of crossovers has been found in infertile men 50, 51 . It was suggested that crossover formation is strictly regulated to avoid aneuploidy 42 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A reduced number of crossovers has been found in infertile men 50, 51 . It was suggested that crossover formation is strictly regulated to avoid aneuploidy 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Our results similarly demonstrate that exposure to ATZ not only delays meiotic synapsis but also affects the number of crossovers. A reduced number of crossovers has been found in infertile men 50 , 51 . It was suggested that crossover formation is strictly regulated to avoid aneuploidy 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Crossover formation is inhibited near centromeres and telomeres in many species including humans (Fig. 3E) (Ottolini et al 2015; Ren et al 2016). Crossovers at centromeres disrupt cohesion in the pericentric region and affect kinetochore orientation.…”
Section: Multiple Layers Of Crossover Regulationmentioning
confidence: 99%
“…For example, crossover formation is not frequently observed near centromere and telomeres, suggesting they may be repressed in these regions. Crossovers at centromere regions lead to aneuploidy in female meiosis and crossovers at telomeres increase azoospermia (Ottolini et al 2015; Ren et al 2016). However, direct testing of how a crossover positioned near centromeres or telomeres might lead to increased errors in chromosome segregation has been challenging in metazoans.…”
Section: Introductionmentioning
confidence: 99%
“…(10) ; however we disagree with the finding of other authors that the OA group had better overall quality embryos than the NOA group (11) . (12) , which may explain, at least partly, the lower embryo development rates observed.…”
Section: Discussionmentioning
confidence: 95%